Active carbon-based water filtering material and preparation method thereof
By developing an activated carbon-based water filter material, using modified coconut shell charcoal and multi-stage pore structure, the problem of difficult removal of organic matter and membrane pollution in micro-polluted water in traditional water treatment technology is solved, and efficient removal of heavy metals and organic matter and improvement of mechanical properties is achieved.
Patent Information
- Application Number
- CN202510195423.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-29
- Filing Date
- 2025-02-21
- Publication Date
- 2025-04-29
AI Technical Summary
Traditional water treatment technology is difficult to effectively remove small molecules and highly hydrophilic organic matter in micro-polluted water, and the membrane pollution problem is serious, limiting the widespread application of membrane technology.
An activated carbon-based water filter material is developed. By mixing modified coconut shell carbon with polyvinyl alcohol and terminal aldehyde-based benzoxazine resin, slurry molding, drying, high-temperature carbon-based water filter material with a multi-stage pore structure is formed.
Through the modification of modified coconut shell charcoal and the formation of multi-stage pore structure, this material significantly improves the adsorption and removal efficiency of heavy metals and organic matters, enhances mechanical properties and conductivity, and reduces film pollution.
Smart Images

Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of activated carbon materials, in particular to an activated carbon-based water filter material and a preparation method thereof. Background Art
[0002] Micro-polluted water refers to water sources that have some water quality indicators that exceed the drinking water hygiene standards due to the reception of industrial wastewater and domestic sewage. The main pollutants in this type of water include organic matter, which is divided into two categories: one is natural organic matter such as humic acid, and the other is artificial organic matter such as pesticides and environmental hormones; in addition, it also contains other harmful substances such as ammonia nitrogen and heavy metal ions. In general, the characteristics of micro-polluted water are that the total concentration of pollutants is relatively low but the types are numerous and the nature is complex.
[0003] The traditional water treatment process mainly includes four stages: coagulation, sedimentation, filtration and disinfection, which are mainly used to remove suspended matter, color and microorganisms in water. However, for organic matter in dissolved state, especially small molecules and highly hydrophilic organic matter, the removal effect of traditional processes is limited because it is difficult for coagulant hydrolysis products to capture these substances. At the same time, disinfection by-products that are harmful to the human body are produced during the disinfection process using chlorine. These limitations mean that traditional methods cannot fully meet the purification needs of micro-polluted water.
[0004] In order to effectively remove organic pollutants from water, researchers have developed a series of advanced water treatment technologies, such as adsorption, membrane separation technology, and advanced oxidation technology. Although membrane separation technology performs well in water treatment, all types of membrane separation processes face a common challenge: membrane fouling. This problem has become a key obstacle to the wider application of membrane technology. To this end, researchers are actively exploring new ways to combine membrane technology with other treatment methods.
[0005] In view of this, the applicant has developed an activated carbon-based water filtration material to solve the above-mentioned membrane fouling problem. Summary of the invention
[0006] In order to solve the existing technical problems, the present invention provides an activated carbon-based water filter material. The activated carbon-based water filter material is prepared by mixing polyvinyl alcohol as a film-forming agent and terminal aldehyde benzoxazine resin as a binder with modified coconut shell charcoal, kneading, molding, drying, and high-temperature carbonization in a mixed gas atmosphere of argon and carbon source gas.
[0007] Furthermore, the terminal aldehyde-terminated benzoxazine resin is obtained by mixing bisphenol A, aniline, 4-aminobutyraldehyde and paraformaldehyde.
[0008] Furthermore, the modified coconut shell charcoal is obtained by modifying coconut shell charcoal with magnesium nitrate and ferric nitrate.
[0009] Furthermore, the carbon source gas includes methane.
[0010] The present invention also provides a method for preparing an activated carbon-based water filter material, comprising the following preparation steps: (1) Mixing: First, place the modified coconut shell activated carbon and PVA in a mixer and vigorously mix them. After adding water 8 to 9 times the mass of PVA, heat it to 90 to 100 °C and stir it at 1300 to 1500 rpm for 10 to 15 min. Then, drop 1.95 to 2 parts by mass of 4M dilute hydrochloric acid, cool it to 25 to 30 °C, then add the terminal aldehyde benzoxazine resin, stir it at room temperature for 1 hour, then heat it to 55 to 65 °C and continue to react for 2.5 to 3.5 hours to obtain a mixture. (2) Clay preparation: Continue to add water to the mixture and roll it to obtain plastic clay. Take out the clay and seal it for aging for 23 to 25 hours to obtain aged clay. (3) Molding: The aged clay material is placed in an extruder for extrusion molding to obtain a tubular membrane blank with an outer diameter of 10 mm and an inner diameter of 6 mm; (4) Drying: Under natural conditions, the tubular membrane blank is placed in the air to dry, thereby obtaining a dried tubular membrane blank; (5) Carbonization: The dried tubular membrane blank is placed in a carbonization furnace in a nitrogen and carbon source gas atmosphere for carbonization at 3 °C / min. -1 The rate is increased from room temperature to the carbonization temperature. After carbonization at a constant temperature for 25 to 35 minutes, it naturally drops to room temperature and is taken out for use.
[0011] Furthermore, the preparation method of the terminal aldehyde-containing benzoxazine resin is as follows: Bisphenol A, aniline, 4-aminobutyraldehyde, and a 37 wt% aqueous solution of paraformaldehyde are dissolved in 5-7 parts by weight of bisphenol A in dioxane, and then refluxed at 80-90°C for 6-14 hours. After cooling to room temperature, the dioxane solvent is removed by rotary evaporation, and then dissolved in ethyl acetate 10-20 times the weight of bisphenol A, washed with 1M sodium hydroxide aqueous solution and deionized water for 3-5 times, and then rotary evaporated to remove water and ethyl acetate to obtain a terminal aldehyde benzoxazine resin; wherein the molar ratio of bisphenol A, aniline, 4-aminobutyraldehyde and paraformaldehyde in the aqueous solution of paraformaldehyde is 1:0.8-1.2:0.8-1.2:4.2-4.6.
[0012] Furthermore, the preparation method of the modified coconut shell activated carbon is as follows: magnesium nitrate, ferric nitrate, coconut shell activated carbon and water are mixed at a mass ratio of 4.2-4.8:4-4.1:100:100 at 1400-1600 rpm for 10-20 min, 1M sodium hydroxide aqueous solution is added to adjust the pH to 10, and 0.01-0.02 times the mass of coconut shell activated carbon ferric nitrate is added dropwise at 20-30 drops / min, followed by aging at 80°C for 3 days, and then drying to obtain modified coconut shell activated carbon.
[0013] Furthermore, in parts by weight, the modified coconut shell activated carbon is 53-67 parts by weight, the PVA is 25-35 parts by weight, and the terminal aldehyde-terminated benzoxazine resin is 8-12 parts by weight.
[0014] Furthermore, the flow ratio of the nitrogen gas to the carbon source gas is 0.3-0.5:1.
[0015] Furthermore, the carbonization temperature is 850-950°C.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The activated carbon-based water filter material prepared by the invention comprises the following steps: firstly, coconut shell charcoal is modified by magnesium nitrate and ferric nitrate to obtain modified coconut shell charcoal; then, polyvinyl alcohol is used as a film-forming agent, terminal aldehyde-containing benzoxazine resin is used as a binder, the modified coconut shell charcoal is mixed, and the mixture is kneaded, formed, dried, and carbonized at high temperature in a mixed gas atmosphere of argon gas and carbon source gas to obtain the activated carbon-based water filter material; wherein the terminal aldehyde-containing benzoxazine resin is obtained by a mixed reaction of bisphenol A, aniline, 4-aminobutyraldehyde and polyformaldehyde.
[0017] Firstly, the coconut shell charcoal is modified with magnesium nitrate and ferric nitrate to form layered double metal hydroxides on the surface of the coconut shell charcoal. The coconut shell charcoal provides a carrier for the layered double metal hydroxides to prevent the aggregation of the layered double metal hydroxides. The coconut shell charcoal can effectively "disperse" the nano-level layered double metal hydroxides, thereby increasing the active adsorption sites of the layered double metal hydroxides for heavy metal ions in the aqueous phase. The presence of layered double metal hydroxides increases the specific surface area of the coconut shell charcoal, and magnesium and iron are formed on the surface of the coconut shell charcoal. When used, magnesium and iron can exchange ions with heavy metal ions to adsorb heavy metal ions. The functional groups of coconut shell biochar are increased after Mg and Fe modification. The complexation and electrostatic attraction of the functional groups improve the adsorption and removal efficiency of heavy metals, and enhance the adsorption effect of activated carbon-based water filtration materials on heavy metals.
[0018] Secondly, polyvinyl alcohol is used as a film-forming agent, and terminal aldehyde-containing benzoxazine resin is used as a binder. After being mixed with modified coconut shell charcoal, the mixture is kneaded, formed, dried, and carbonized at high temperature in a mixed gas atmosphere of argon and carbon source gas to obtain an activated carbon-based water filter material; the addition of polyvinyl alcohol can effectively bond the terminal aldehyde-containing benzoxazine resin and the modified coconut shell charcoal, and the hydroxyl group on the polyvinyl alcohol reacts and condenses with the aldehyde group of n-butyraldehyde on the terminal aldehyde-containing benzoxazine resin to form a mixture containing polyvinyl butyral, and the polyvinyl alcohol molecular chain and the terminal aldehyde-containing benzoxazine resin molecular chain are tightly cross-linked together. Subsequently, after high-temperature carbonization, the polyvinyl butyral is decomposed into small molecular gas by heat and volatilized, forming channels in the activated carbon-based water filter material, forming an activated carbon-based water filter material with a multi-level pore structure of macropores, mesopores and micropores, which increases the permeability and adsorption properties of the activated carbon-based water filter material; but with the increase of polyvinyl butyral The high-temperature decomposition and volatilization of the terminal aldehyde-containing benzoxazine resin and the carbon skeleton formed after carbonization are prone to collapse, resulting in poor mechanical properties of the activated carbon-based water filter material. The activated carbon-based water filter material is carbonized at high temperature in a mixed gas atmosphere of argon and carbon source gas. The carbon source gas is carbonized under the action of ferric nitrate that is not completely aged on the surface of coconut shell charcoal. Carbon nanowires are generated in situ between the carbon skeleton formed after carbonization of the terminal aldehyde-containing benzoxazine resin and the coconut shell charcoal to firmly connect the carbon skeleton and the coconut shell charcoal together, which not only ensures the mechanical properties of the activated carbon-based water filter material, but also enhances the conductivity of the activated carbon-based water filter material. When the activated carbon-based water filter material is used as the anode material and the annular carbon sheet is used as the cathode and is placed in a tank storing wastewater to be treated for electrocatalytic oxidation, the organic pollutants adsorbed on the activated carbon-based water filter material can be degraded, and algae, bacteria, etc. are inactivated, thereby reducing the membrane pollution phenomenon of the activated carbon-based water filter material. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below in conjunction with examples, but the following examples should not be construed as limiting the present invention.
[0020] The polyvinyl alcohol used in the examples and comparative examples of the present invention is PVA-1799 produced by Tianjin Fuchen Chemical Reagent Factory; the industrial grade coconut shell activated carbon is obtained from Shandong Huatan Environmental Protection Technology Co., Ltd. Example 1
[0021] A method for preparing an activated carbon-based water filter material comprises the following preparation steps: (1) Mixing: First, 53 parts by weight of modified coconut shell activated carbon and 35 parts by weight of PVA were vigorously mixed in a mixer, and then 8 times the weight of water of PVA was added, and the mixture was heated to 90°C and stirred at 1300 rpm for 10 min. Then, 1.95 parts by weight of 4M dilute hydrochloric acid was added dropwise, and the mixture was cooled to 25°C. Then, 12 parts by weight of terminal aldehyde-containing benzoxazine resin was added, and the mixture was stirred and reacted at room temperature for 1 h. Then, the mixture was heated to 55°C and the reaction was continued for 2.5 h to obtain a mixture. (2) Clay preparation: Continue to add water to the mixture and roll it to obtain plastic clay. Take out the clay and seal it for aging for 23 hours to obtain aged clay. (3) Molding: The aged clay material is placed in an extruder for extrusion molding to obtain a tubular membrane blank with an outer diameter of 10 mm and an inner diameter of 6 mm; (4) Drying: Under natural conditions, the tubular membrane blank is placed in the air to dry, thereby obtaining a dried tubular membrane blank; (5) Carbonization: The dried tubular membrane blank is placed in a carbonization furnace in a nitrogen and carbon source gas atmosphere for carbonization at 3 °C / min. -1 The rate was increased from room temperature to 850 °C, and after constant temperature carbonization for 25 min, the temperature was naturally lowered to room temperature and then taken out for use to obtain an activated carbon-based water filtration material; wherein, the flow ratio of nitrogen and carbon source gas was 0.3:1, and the flow rate of nitrogen was 300 mL / min.
[0022] The preparation method of the terminal aldehyde-containing benzoxazine resin is as follows: Bisphenol A, aniline, 4-aminobutyraldehyde, and a 37 wt% aqueous solution of paraformaldehyde are dissolved in 5 parts by mass of bisphenol A per dioxane, and then refluxed at 80°C for 6 hours. After cooling to room temperature, the dioxane solvent is removed by rotary evaporation, and then dissolved in ethyl acetate 10 times the mass of bisphenol A, washed three times with 1M sodium hydroxide aqueous solution and deionized water, and then rotary evaporation is continued to remove water and ethyl acetate to obtain a terminal aldehyde benzoxazine resin; wherein the molar ratio of bisphenol A, aniline, 4-aminobutyraldehyde and paraformaldehyde in the aqueous solution of paraformaldehyde is 1:0.8:0.8:4.2.
[0023] The polyvinyl alcohol is PVA-1799 produced by Tianjin Fuchen Chemical Reagent Factory; The preparation method of the modified coconut shell activated carbon is as follows: magnesium nitrate, ferric nitrate, coconut shell activated carbon and water are mixed at a mass ratio of 4.2:4:100:100 at 1400 rpm for 10 minutes, a 1M sodium hydroxide aqueous solution is added to adjust the pH to 10, and 0.01 times the mass of coconut shell activated carbon ferric nitrate is added dropwise at 20 drops / min, followed by aging at 80° C. for 3 days, and then drying to obtain the modified coconut shell activated carbon. Example 2
[0024] A method for preparing an activated carbon-based water filter material comprises the following preparation steps: (1) Mixing: First, 70 parts by weight of modified coconut shell activated carbon and 30 parts by weight of PVA were placed in a mixer and vigorously mixed. After adding 8.5 times the weight of PVA in water, the temperature was raised to 95°C and stirred at 1400 rpm for 13 min. Then, 1.98 parts by weight of 4M dilute hydrochloric acid was added dropwise. The mixture was cooled to 28°C. Then, 10 parts by weight of terminal aldehyde benzoxazine resin was added. The mixture was stirred and reacted at room temperature for 1 h. Then, the temperature was raised to 60°C and the reaction was continued for 3 h to obtain a mixture. (2) Clay preparation: Continue to add water to the mixture and roll it to obtain plastic clay. Take out the clay and seal it for aging for 24 hours to obtain aged clay. (3) Molding: The aged clay material is placed in an extruder for extrusion molding to obtain a tubular membrane blank with an outer diameter of 10 mm and an inner diameter of 6 mm; (4) Drying: Under natural conditions, the tubular membrane blank is placed in the air to dry, thereby obtaining a dried tubular membrane blank; (5) Carbonization: The dried tubular membrane blank is placed in a carbonization furnace in a nitrogen and carbon source gas atmosphere for carbonization at 3 °C / min. -1 The rate was increased from room temperature to 900 °C, and after constant temperature carbonization for 30 min, it naturally dropped to room temperature and was taken out for use to obtain an activated carbon-based water filtration material; wherein, the flow ratio of nitrogen and carbon source gas was 0.4:1, and the flow rate of nitrogen was 300 mL / min.
[0025] The preparation method of the terminal aldehyde-containing benzoxazine resin is as follows: Bisphenol A, aniline, 4-aminobutyraldehyde, and a 37 wt% aqueous solution of paraformaldehyde are dissolved in 6 parts by mass of bisphenol A per dioxane, and then refluxed at 85°C for 10 hours. After cooling to room temperature, the dioxane solvent is removed by rotary evaporation, and then dissolved in ethyl acetate 15 times the mass of bisphenol A, washed 4 times with 1M sodium hydroxide aqueous solution and deionized water, and then rotary evaporation is continued to remove water and ethyl acetate to obtain a terminal aldehyde benzoxazine resin; wherein the molar ratio of bisphenol A, aniline, 4-aminobutyraldehyde and paraformaldehyde in the aqueous solution of paraformaldehyde is 1:1:1:4.4.
[0026] The polyvinyl alcohol is PVA-1799 produced by Tianjin Fuchen Chemical Reagent Factory; The preparation method of the modified coconut shell activated carbon is as follows: magnesium nitrate, ferric nitrate, coconut shell activated carbon and water are mixed at a mass ratio of 4.6:4.05:100:100 at 1500 rpm for 15 minutes, a 1M sodium hydroxide aqueous solution is added to adjust the pH to 10, and ferric nitrate of 0.015 times the mass of the coconut shell activated carbon is added dropwise at 25 drops / min, followed by aging at 80° C. for 3 days, and then drying to obtain the modified coconut shell activated carbon. Example 3
[0027] A method for preparing an activated carbon-based water filter material comprises the following preparation steps: (1) Mixing: First, 67 parts by weight of modified coconut shell activated carbon and 25 parts by weight of PVA were placed in a mixer and vigorously mixed. After adding water 9 times the weight of PVA, the temperature was raised to 100°C and stirred at 1500 rpm for 15 min. Then, 2 parts by weight of 4M dilute hydrochloric acid was added dropwise. The mixture was cooled to 30°C and then 8 parts by weight of terminal aldehyde-containing benzoxazine resin was added. The mixture was stirred and reacted at room temperature for 1 h. The mixture was then heated to 65°C and continued to react for 3.5 h to obtain a mixture. (2) Clay preparation: Continue to add water to the mixture and roll it to obtain a plastic clay material. Take out the clay preparation and seal it for aging for 25 hours to obtain an aged clay material. (3) Molding: The aged clay material is placed in an extruder for extrusion molding to obtain a tubular membrane blank with an outer diameter of 10 mm and an inner diameter of 6 mm; (4) Drying: Under natural conditions, the tubular membrane blank is placed in the air to dry, thereby obtaining a dried tubular membrane blank; (5) Carbonization: The dried tubular membrane blank is placed in a carbonization furnace in a nitrogen and carbon source gas atmosphere for carbonization at 3 °C / min. -1 The rate was increased from room temperature to 950 °C, and after constant temperature carbonization for 35 min, the temperature was naturally lowered to room temperature and then taken out for use to obtain an activated carbon-based water filtration material; wherein, the flow ratio of nitrogen and carbon source gas was 0.5:1, and the flow rate of nitrogen was 300 mL / min.
[0028] The preparation method of the terminal aldehyde-containing benzoxazine resin is as follows: Bisphenol A, aniline, 4-aminobutyraldehyde, and a 37 wt% aqueous solution of paraformaldehyde are dissolved in 7 parts by mass of bisphenol A per 100% by weight of dioxane, and then refluxed at 90°C for 14 hours. After cooling to room temperature, the dioxane solvent is removed by rotary evaporation, and then dissolved in ethyl acetate 20 times the mass of bisphenol A, washed 5 times with 1M sodium hydroxide aqueous solution and deionized water, and then rotary evaporation is continued to remove water and ethyl acetate to obtain a terminal aldehyde-containing benzoxazine resin; wherein the molar ratio of bisphenol A, aniline, 4-aminobutyraldehyde and paraformaldehyde in the aqueous solution of paraformaldehyde is 1:1.2:1.2:4.6.
[0029] The polyvinyl alcohol is PVA-1799 produced by Tianjin Fuchen Chemical Reagent Factory; The preparation method of the modified coconut shell activated carbon is as follows: magnesium nitrate, ferric nitrate, coconut shell activated carbon and water are mixed at a mass ratio of 4.8:4.1:100:100 at 1600 rpm for 20 minutes, a 1M sodium hydroxide aqueous solution is added to adjust the pH to 10, and ferric nitrate in an amount of 0.02 times the mass of the coconut shell activated carbon is added dropwise at 30 drops / min, followed by aging at 80° C. for 3 days, and then drying to obtain the modified coconut shell activated carbon. Comparative Example 1
[0030] The difference between Comparative Example 1 and Example 2 is that only magnesium nitrate is used to modify coconut shell activated carbon; the remaining steps and ingredients are the same as those in Example 2. Comparative Example 2
[0031] The difference between Comparative Example 2 and Example 2 is that only coconut shell activated carbon is modified by iron nitrate; the remaining steps and components are the same as those in Example 2. Comparative Example 3
[0032] The only difference between Comparative Example 3 and Example 2 is that coconut shell activated carbon is used to prepare the activated carbon-based water filter material; the remaining steps and ingredients are the same as those in Example 2. Comparative Example 4
[0033] The difference between Comparative Example 4 and Example 2 is that only benzoxazine resin is used to prepare the activated carbon-based water filter material; the remaining steps and components are the same as those in Example 2. Comparative Example 5
[0034] The difference between Comparative Example 5 and Example 2 is that the activated carbon-based water filter material is prepared by carbonization only under argon atmosphere; the remaining steps and components are the same as those in Example 2. Effect example
[0035] Mechanical strength: With reference to standard HG / T2782-2011, the YHKC-2A particle strength tester produced by Taizhou Yinhe Instrument Factory was used for testing. Before the test, the activated carbon-based water filtration materials prepared in the embodiments and comparative examples were cut into 1 cm lengths, and the two ends were polished flat with sandpaper. During the test, the activated carbon-based water filtration materials were placed horizontally on the test bench, and the pressure was slowly increased until the carbon membrane broke. The limit pressure of each sample (5 parallel samples) was recorded, and the average value was taken.
[0036] Methylene blue adsorption value test: According to the national standard GB / T12496.10-1999, a methylene blue solution with a concentration of 1.5g was accurately prepared. Weigh 0.1g (accurate to 0.001g) of the activated carbon-based water filter material obtained by the dry legal person embodiment and the comparative example and place it in a 250mL conical flask with a ground mouth stopper, add an appropriate amount of methylene blue solution with a burette, and immediately place it on an oscillator to oscillate after the sample is completely wetted. Observe the decolorization rate of the solution, and add a small amount of methylene blue solution in sequence until the solution no longer decolorizes. The volume of methylene blue solution used for titration is the methylene blue adsorption value of the sample, which is expressed in mL / 0.1g, and can also be expressed in mg / g, which is 15 times the methylene blue value.
[0037] Electrochemical impedance: The activated carbon-based water filter materials prepared in the examples and comparative examples were cut into 10 cm lengths, and electrochemical impedance spectroscopy was performed under open circuit voltage with a frequency range of 0.1-106 Hz and an electrolyte of 0.1 mol·L -1 Sodium sulfate aqueous solution.
[0038] The activated carbon-based water filter material prepared in the examples and comparative examples was cut into small sections of 6 cm in length, ultrasonically cleaned in deionized water for 10 minutes, and then placed in a forced air drying oven at 120°C for 2 hours; the activated carbon-based water filter material was used as the anode and placed in the center of the stock liquid tank, and the annular titanium sheet was used as the cathode and placed on the inner wall of the stock liquid tank, and connected to a DC power supply with a wire to provide an external DC electric field. The device operates in a dead-end filtration mode, with one end of the tubular activated carbon-based water filter material sealed and the other end connected to a hose. The peristaltic pump provides power to pump the waste liquid to be treated from the stock liquid tank to the surface of the activated carbon-based water filter material, and through the membrane pores of the activated carbon-based water filter material to the inside of the carbon membrane, and then along the pipeline through the peristaltic pump to reach the water outlet tank to obtain the permeate. During the operation, the DC power supply voltage can be adjusted, and the liquid flow rate is fixed at 1 mL min -1 ; The calculation formula for the permeation flux of activated carbon-based water filtration materials is as follows: ; Where: P is the permeability coefficient (L·h -1 ·m -2 bar -1 ); V is the volume of the collected permeate (mL); t is the permeation time (s); S is the effective area of the carbon membrane (cm 2 ); ΔP is the transmembrane pressure difference (Pa); The concentration of heavy metal ions in the solution was tested using an AFG flame atomic absorption spectrometer (TAS-990super). The calculation formula for the adsorption of heavy metal ions is as follows: ; Where B is the heavy metal ion adsorption capacity of TCM (mg g -1 );c 0 is the heavy metal ion concentration of the stock solution (mg·L -1 );c t is the heavy metal ion concentration of the treated solution (mg·L -1 ); V is the volume of the solution (mL), m is the mass of TCM (g); where the lead ion concentration in the test stock solution is 100 mg / L.
[0039] The number of bacteria in water was determined by plate counting method, and the calculation formula of bacteria removal rate is as follows: ;;
[0040] Where RTPC is the bacterial removal rate (%); TPCF is the total bacterial count in the stock solution (cfu); TPCP is the bacterial count in the permeate (cfu); the bacterial count in the stock solution is 13 cfu·mL -1 .
[0041] The absorbance of the permeate was tested using a UV-visible spectrophotometer, and the removal rate of organic matter in the wastewater was calculated according to the Lambert-Beer law. The calculation formula for the removal rate of organic matter is as follows: ;
[0042] Where: R is the removal rate of target organic matter (%); C 0 is the concentration of the target organic matter in the stock solution (mg·L -1 ); C e is the concentration of target organic matter in the permeate (mg·L -1 ); The concentration of the target organic substance Rhodamine B in the stock solution is 200 mg / L.
[0043] Table 1 below shows the performance test analysis results of the activated carbon-based water filtration materials prepared using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0044] Table 1
[0045] From the comparison of Example 2 with Comparative Examples 1 to 5 in Table 1, it can be found that the activated carbon-based water filter material prepared in the embodiment has good heavy metal adsorption, mechanical properties, electrochemical impedance, antibacterial properties, and organic matter removal performance, and a higher permeation flux; Compared with Comparative Examples 1 to 3 and 5, Example 2 finds that the activated carbon-based water filter material prepared by using magnesium nitrate and ferric nitrate modified coconut shell biochar as raw materials and high-temperature carbonization in a mixed gas atmosphere of argon and carbon source gas is used to prepare the activated carbon-based water filter material, and the heavy metal adsorption, mechanical properties, electrochemical impedance, antibacterial properties, and organic matter removal performance of the prepared activated carbon-based water filter material are good; Compared with Comparative Example 4, Example 2 finds that the activated carbon-based water filter material prepared by using terminal aldehyde benzoxazine resin as a binder is good in mechanical properties and organic matter adsorption performance, and a higher permeation flux.
[0046] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
Claims
1. An activated carbon-based water filter material, characterized in that: The activated carbon-based water filter material is obtained by mixing polyvinyl alcohol as a film-forming agent and terminal aldehyde benzoxazine resin as a binder with modified coconut shell charcoal, kneading, molding, drying, and high-temperature carbonization in a mixed gas atmosphere of argon and carbon source gas.
2. The activated carbon-based water filter material according to claim 1, characterized in that: The terminal aldehyde-terminated benzoxazine resin is obtained by mixing bisphenol A, aniline, 4-aminobutyraldehyde and paraformaldehyde.
3. The activated carbon-based water filter material according to claim 1, characterized in that: The modified coconut shell charcoal is obtained by modifying the coconut shell charcoal with magnesium nitrate and ferric nitrate.
4. The activated carbon-based water filter material according to claim 1, characterized in that: The carbon source gas includes methane.
5. A method for preparing an activated carbon-based water filter material according to any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: (1) Mixing: First, place the modified coconut shell activated carbon and PVA in a mixer and vigorously mix them. After adding water 8 to 9 times the mass of PVA, heat it to 90 to 100 °C and stir it at 1300 to 1500 rpm for 10 to 15 min. Then, drop 1.95 to 2 parts by mass of 4M dilute hydrochloric acid, cool it to 25 to 30 °C, then add the terminal aldehyde benzoxazine resin, stir it at room temperature for 1 hour, then heat it to 55 to 65 °C and continue to react for 2.5 to 3.5 hours to obtain a mixture. (2) Clay preparation: Continue to add water to the mixture and roll it to obtain plastic clay. Take out the clay and seal it for aging for 23 to 25 hours to obtain aged clay. (3) Molding: The aged clay material is placed in an extruder for extrusion molding to obtain a tubular membrane blank with an outer diameter of 10 mm and an inner diameter of 6 mm; (4) Drying: Under natural conditions, the tubular membrane blank is placed in the air to dry, thereby obtaining a dried tubular membrane blank; (5) Carbonization: The dried tubular membrane blank is placed in a carbonization furnace in a nitrogen and carbon source gas atmosphere for carbonization at 3 °C / min. -1 The rate is increased from room temperature to the carbonization temperature. After carbonization at a constant temperature for 25 to 35 minutes, it naturally drops to room temperature and is taken out for use.
6. The method for preparing an activated carbon-based water filter material according to claim 5, characterized in that: The preparation method of the terminal aldehyde-containing benzoxazine resin is as follows: Bisphenol A, aniline, 4-aminobutyraldehyde, and a 37 wt% aqueous solution of paraformaldehyde are dissolved in 5-7 parts by weight of bisphenol A in dioxane, and then refluxed at 80-90°C for 6-14 hours. After cooling to room temperature, the dioxane solvent is removed by rotary evaporation, and then dissolved in ethyl acetate 10-20 times the weight of bisphenol A, washed with 1M sodium hydroxide aqueous solution and deionized water for 3-5 times, and then rotary evaporated to remove water and ethyl acetate to obtain a terminal aldehyde-containing benzoxazine resin; wherein the molar ratio of bisphenol A, aniline, 4-aminobutyraldehyde, and paraformaldehyde in the aqueous solution of paraformaldehyde is 1:0.8-1.2:0.8-1.2:4.2-4.
6.
7. The method for preparing an activated carbon-based water filter material according to claim 5, characterized in that: The preparation method of the modified coconut shell activated carbon is as follows: magnesium nitrate, ferric nitrate, coconut shell activated carbon and water are mixed at a mass ratio of 4.2-4.8:4-4.1:100:100 at 1400-1600 rpm for 10-20 minutes, a 1M sodium hydroxide aqueous solution is added to adjust the pH to 10, and ferric nitrate of 0.01-0.02 times the mass of coconut shell activated carbon is added dropwise at 20-30 drops / min, followed by aging at 80°C for 3 days, and then drying to obtain the modified coconut shell activated carbon.
8. The method for preparing an activated carbon-based water filter material according to claim 5, characterized in that: In terms of weight, the modified coconut shell activated carbon is 53-67 parts by weight, the PVA is 25-35 parts by weight, and the terminal aldehyde-containing benzoxazine resin is 8-12 parts by weight.
9. The method for preparing an activated carbon-based water filter material according to claim 5, characterized in that: The flow ratio of the nitrogen gas to the carbon source gas is 0.3-0.5:
1.
10. The method for preparing an activated carbon-based water filter material according to claim 5, characterized in that: The carbonization temperature is 850-950°C.